Beyond the Stable Image of Institutions: Using Institutional Analysis to Tackle Classic Questions in Institutional Theory - Bouilloud, Jean-Philippe; Pérezts, Mar; Viale, Thierry; Schaepelynck, Valentin (Organization studies, 2020)
Although institutions are subject to constant change, we retain a stable image of them. Consequently, should they be considered as objects or processes? Notwithstanding its success, institutional theory still faces theoretical challenges to account simultaneously for change and stability, agency and structure. Following recent calls to integrate other perspectives on how we think about institutions, we draw on institutional analysis – a stream that has flourished in Europe and Latin America – to propose a radical and comprehensive conception of the institution as a locus of tension between the instituting (by which institutions are formed) and the instituted (temporarily stabilized forms). Since there is permanent tension between them, the institution itself can never be a stable object. It is constantly evolving, being either reinforced or destabilized. This research enriches the theoretical dialogue between organizational institutionalism and institutional analysis, two streams that have hitherto displayed little cross-fertilization. First, it contributes to rethinking the nature of institutions by emphasizing the role of the social imaginary, thus improving our understanding of the under-theorized role of imagination in institutionalization processes. Second, by placing the dynamic tension between the instituted and the instituting at the core of institutional theories, we answer calls to reclaim their missing critical dimension. Furthermore, this results in a methodological implication: the clinical approach of institutional analysis involving the intervention of researchers allows us to further embed institutional theories in organizational practice.